2018
DOI: 10.1016/j.exer.2018.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability of corneal endothelial cells to mechanical trauma from indentation forces assessed using contact mechanics and fluorescence microscopy

Abstract: Corneal endothelial cell (CEC) loss occurs from tissue manipulation during anterior segment surgery and corneal transplantation as well as from contact with synthetic materials like intraocular lenses and tube shunts. While several studies have quantified CEC loss for specific surgical steps, the vulnerability of CECs to isolated, controllable and measurable mechanical forces has not been assessed previously. The purpose of this study was to develop an experimental testing platform where the susceptibility of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…In young adults, the endothelial cell density (ECD) within a healthy cornea is approximately 3,000–4,000 cells/mm 2 . However, an abnormal cornea loses its ability to pump sufficient water to maintain its function when ECD decreases below 750–500 cells/mm 2 ( Ramirez-Garcia et al, 2018 ).…”
Section: Corneal Structure and Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In young adults, the endothelial cell density (ECD) within a healthy cornea is approximately 3,000–4,000 cells/mm 2 . However, an abnormal cornea loses its ability to pump sufficient water to maintain its function when ECD decreases below 750–500 cells/mm 2 ( Ramirez-Garcia et al, 2018 ).…”
Section: Corneal Structure and Functionsmentioning
confidence: 99%
“…Furthermore, mechanical compression interferes with the maintenance of normal stromal structures ( Figure 3C ). Ramirez-Garcia et al (2018) evaluated the response of corneal endothelial cells to the indentation forces in vitro and found that the damage/apoptosis of CEnCs increased and ECD decreased significantly when the contact pressure exceeded 5.7 kPa (42.75 mmHg). When acute ocular hypertension (∼82.6 mmHg for 2 h) was induced, the ECD was significantly decreased, and CEnCs became irregular and multiform with disrupted ZO-1 and F-actin ( Li et al, 2017 ).…”
Section: The Impact Of Tensile and Compressive Stressesmentioning
confidence: 99%
“…19 When cataracts are extracted, for example, lens fragments can collide with the endothelium. 20 New approaches, such as using newer platforms to minimize power, changing energy mode, using the softshell technique to protect the CECs, and pre-chopping the nucleus with manual methods or the femtosecond laser, can reduce trauma to CEC. 21 , 22 , 23 Chen et al.…”
Section: Discussionmentioning
confidence: 99%